Experimental study on the hydro-thermal-deformation characteristics of cement-stabilized soil exposed to freeze–thaw cycles - Lu, Jianguo; Tan, Liling; Yang, Huohai; Wan, Xusheng; Wang, Yindong; Yan, Zhongrui (Frontiers in Earth Science, 2023)
The exploration of the hydro-thermal characteristics and deformation behaviors of cement-stabilized soils is important for the prevention and control of freeze–thaw damage in cold region engineering. This study used six groups of cement-stabilized soil samples with different cement contents (i.e., 3%, 6%, 9%, 12%, 15%, and 18%) to investigate the variations in soil temperature, volumetric unfrozen water content, deformation, freezing temperature, and dry density. The results showed that the temperatures of the cement-stabilized soil samples during the freezing and thawing processes can be categorized into three stages and that the freezing temperature decreased with increasing cement content. Moreover, the cement content and ambient temperature significantly affected the volumetric unfrozen water content of the cement-stabilized soil samples during the freeze–thaw cycles, and the soil temperatures corresponding to the peak hysteresis degree were relatively consistent with the freezing temperature. The residual volumetric unfrozen water content primarily depended not only on the cement content but also on the freezing condition. Although the variations in volumetric unfrozen water contents during the freezing and thawing processes were similar, the ranges in temperature change differed significantly, particularly in the drastic phase transition zone. Additionally, adding cement into soils effectively inhibited deformation, mainly due to the dual positive effects of the liquid water reduction owing to hydration reaction and structure compaction owing to the filling of hydration products.